Business Plan : AZ Jaya Trading / Fatin Nadia Nursyakirah Mohd Razlan - Mohd Razlan, Fatin Nadia Nursyakirah (2021)
An entrepreneur has many choices to choose their fields of business because there are a lot of choices that they can explore. As we can see today, there are many cosmetics entrepreneur, fast food entrepreneur and branches entrepreneur. In the short term, we can conclude that every field in business will have their subcategories and will expand to all over the world once it become successful. As for this case study, I choose construction, supplying and services industry because it attracts me to get to know more about how they work. AZ Jaya Trading is the company that manage to attract me which owned by Mrs. Nurasyikin binti Mohamed. I get all the information about this company from Mr. Khairul Izzat bin Ibrahim. He is the assistant manager of AZ Jaya Trading and he did all works that related to AZ Jaya from 2016. He helps Mrs. Nurasyikin to deal with clients and planning the project. He is married to Nurul Ayunie binti Azmi and blessed with two beautiful children. Mrs. Nurasyikin competencies are initiative, persistence, concern for high quality of work, using influence strategies, and commitment to work contract. The company strength is they will make it possible to provide supply that the client request and will manage the project smoothly. However, the weakness is they are offering three types of job which are construction, supplying and services that made them overlap sometimes. At the end, they manage to overcome their weakness by planning the project one by one so that they do not have any abandoned project. In the meantime, because they are offering many types of services, they got many opportunities to deal with lots of clients.